Epitope spreading: lessons from autoimmune skin diseases. - Chan, L; Vanderlugt, C; Hashimoto, T; Nishikawa, T; Zone, J; Black, M; Wojnarowska, F; Stevens, SR; Chen, M; Fairley, J; Woodley, D; Miller, S; et al. (1998)
Autoimmune diseases are initiated when patients develop aberrant T and/or B cell responses against self proteins. These responses presumably are directed to single immunogenic epitopes on these proteins. Recent data in animal models of autoimmune diseases suggest that the targets of immune responses in autoimmunity do not remain fixed, but can be extended to include other epitopes on the same protein or other proteins in the same tissue, a phenomenon termed "epitope spreading." The "epitope spreading" phenomenon also applies to situations in which tissue damage from a primary inflammatory process causes the release and exposure of a previously "sequestered" antigen, leading to a secondary autoimmune response against the newly released antigen. In experimental autoimmune animal diseases, "epitope spreading" seems to have significant physiologic importance in determining the course and duration of disease. In this paper, we review the current concepts in animal models of autoimmune diseases in order to define the "epitope spreading" phenomenon, and we then propose how this phenomenon might play a significant role in the development and the course of autoimmune skin diseases. Hopefully, an understanding of "epitope spreading" will help the dermatology community to better understand the pathogenesis of autoimmune skin diseases and to rationally fashion disease-specific immune therapy in the future.